Photoelectrochemical Properties and Its Application of Nano-TiO2/ Boron-doped Diamond Heterojunction Electrode Material - Han, Yanhe; Ruan, Xiuli; Chen, Jiaqing; Zhang, Haimin; Zhao, Huijun; Zhang, Shanqing (Asian Journal of Chemistry, 2013)
Like titanium dioxide (TiO2), boron-doped diamond (BDD) is one of the most popular functional materials in recent years. In this work, TiO2/BDD heterojunction electrodes were prepared by dip-coating TiO2 nanoparticles onto BDD electrodes. XRD patterns of these electrodes suggest that the mixed-phase TiO2/BDD heterojunction electrode with anatase and rutile can be obtained at 700 ºC, named as mixed-phase TiO2/BDD electrode. However, the TiO2/BDD heterojunction electrode prepared at 450 ºC has only anatase phase TiO2, named as pure-anatase TiO2/BDD electrode. SEM images indicate that TiO2 nanoparticles with ca. 20 nm were both immobilized continuously and uniformly onto the BDD electrode whether at 700 ºC or 450 ºC. The photoelectrocatalytic activity of mixed-phase TiO2/BDD electrode is 3-fold of that obtained at pure-anatase TiO2/BDD electrode, indicating that mixed-phase TiO2/BDD electrode is more effective to use to degrade and/or detect the organic compounds. Comparing with the TiO2/ITO electrode, the TiO2/BDD electrode presents an excellent chemical stability. The detection of glucose and KHP in the solution indicates that the steady-state net photocurrent in the range of concentration monitored presents superiorly linear relationship to the concentration of glucose and KHP. Therefore, the mixed-phase TiO2/BDD electrode may be used as a high effective sensing material for the detection of organic compounds.